Willow Extract (Salix cortex), a Basic Substance of Agronomical Interests - Deniau, M. G.; Bonafos, R.; Chovelon, M.; Parvaud, C-E.; Furet, A.; Bertrand, C.; Marchand, P. A. (International Journal of Bio-resource and Stress Management, 2019)
Salix spp. cortex is a bark extract from the common plant willow including S. purpurea L., S. daphnoides Vill. and S. fragilis L, traditionally used in human medicine (i.e. for acetylsalicylic acid usually called aspirin). It is an approved basic substance with fungicidal properties under agricultural EU pesticide regulation (Regulation (EC) no 1107/2009) since 2015. Currently, its approved uses are for arboriculture and viticulture. An initial use extension to allow nurseries to use it as a plant growth regulator is being evaluated by the EU regulatory assessment organisation. Willow water helps cuttings to root, due to its indole butyric acid content, which is a growth hormone (plant growth regulator) in the auxin family and generally chemically synthesized for this purpose. Recently, fungicide usages for the vegetable and fruit market (tomatoes, berries and kiwis) have been submitted to the EU Commission for evaluation. Initial main field trials to demonstrate its plant protection properties were coordinated in France by the 4P project “Protection des Plantes Par les Plantes” (Plant Protection by Plants) between 2010 and 2013 but additional field trials were collected. We detail in this study the results obtained and all the uses of this extract as a plant protection product, including inducing rooting. In addition, we describe the full approval processes for the basic substance Salix spp. cortex and these extensions of use, covered by the Article 23 of the plant protection regulation in EU.